Research in economic history. Vol. 32 - Hanes, Christopher; Wolcott, Susan K. (Research in economic history,, 2016)
Research in Economic History is a refereed journal, specializing in economic history, in the form of a book. This volume contains Louis Cain and Brooks Kaiser, "A Century of Environmental Legislation"; Stefano Fenoaltea, "The Measurement of Production: Lessons from the Engineering Industry in Italy, 1911"; Farley Grubb, "Is Paper Money Just Paper Money? Experimentation and Variation in Paper Monies Issued by the American Colonies from 1690 to 1775"; Oriol Sabate, "New Quantitative Estimates of Long-Term Military Spending in Spain, 1850-2009"; Eric Schneider, "Health, Gender and the Household: Children's Growth in the Marcella Street Home, Boston MA and the Ashford School, London, UK"; Ta-Chen Wang, "Entry, Competition and Terms of Credit in Early American Banking."